Intensity-Dependent Effects of Acute Exercise on Executive Function - Aylin Mehren; Cecilia Diaz Luque; Mirko Brandes; Alexandra P. Lam; Christiane M. Thiel; Alexandra Philipsen; Jale Özyurt (Neural Plasticity)
Numerous studies suggest beneficial effects of aerobic exercise at moderate intensity on cognition, while the effects of high-intensity exercise are less clear. This study investigated the acute effects of exercise at moderate and high intensities on executive functions in healthy adults, including functional MRI to examine the underlying neural mechanisms. Furthermore, the association between exercise effects and cardiorespiratory fitness was examined. 64 participants performed in two executive function tasks (flanker and Go/No-go tasks), while functional MR images were collected, following two conditions: in the exercise condition, they cycled on an ergometer at either moderate or high intensity (each n=32); in the control condition, they watched a movie. Differences in behavioral performance and brain activation between the two conditions were compared between groups. Further, correlations between cardiorespiratory fitness and exercise effects on neural and behavioral correlates of executive performance were calculated. Moderate exercise compared to high-intensity exercise was associated with a tendency towards improved behavioral performance (sensitivity index d′) in the Go/No-go task and increased brain activation during hit trials in areas related to executive function, attention, and motor processes (insula, superior frontal gyrus, precentral gyrus, and supplementary motor area). Exercise at high intensity was associated with decreased brain activation in those areas and no changes in behavioral performance. Exercise had no effect on brain activation in the flanker task, but an explorative analysis revealed that reaction times improved after high-intensity exercise. Higher cardiorespiratory fitness was correlated with increased brain activation after moderate exercise and decreased brain activation after high-intensity exercise. These data show that exercise at moderate vs. high intensity has different effects on executive task performance and related brain activation changes as measured by fMRI and that cardiorespiratory fitness might be a moderating factor of acute exercise effects. Thus, our results may contribute to further clarify the neurophysiological mechanisms underlying the beneficial effects of exercise on cognition.